Characterization of the l‐alanine exporter AlaE of Escherichia coli and its potential role in protecting cells from a toxic‐level accumulation of l‐alanine and its derivatives. Issue 4 (13th June 2015) - Kim, Seryoung; Ihara, Kohei; Katsube, Satoshi; Hori, Hatsuhiro; Ando, Tasuke; Isogai, Emiko; Yoneyama, Hiroshi
Abstract We previously reported that the alaE gene of Escherichia coli encodes the l‐alanine exporter AlaE. The objective of this study was to elucidate the mechanism of the AlaE exporter. The minimum inhibitory concentration of l‐alanine and l‐alanyl‐l‐alanine in alaE‐deficient l‐alanine‐nonmetabolizing cells MLA301ΔalaE was 4‐ and >4000‐fold lower, respectively, than in the alaE‐positive parent cells MLA301, suggesting that AlaE functions as an efflux pump to avoid a toxic‐level accumulation of intracellular l‐alanine and its derivatives. Furthermore, the growth of the alaE‐deficient mutant derived from the l‐alanine‐metabolizing strain was strongly inhibited in the presence of a physiological level of l‐alanyl‐l‐alanine. Intact MLA301ΔalaE and MLA301ΔalaE/pAlaE cells producing plasmid‐borne AlaE, accumulated approximately 200% and 50%, respectively, of the [3H]l‐alanine detected in MLA301 cells, suggesting that AlaE exports l‐alanine. When 200 mmol/L l‐alanine‐loaded inverted membrane vesicles prepared from MLA301ΔalaE/pAlaE were placed in a solution containing 200 mmol/L or 0.34 μmol/L l‐alanine, energy‐dependent [3H]l‐alanine accumulation occurred under either condition. This energy‐dependent uphill accumulation of [3H]l‐alanine was strongly inhibited in the presence of carbonyl cyanide m‐chlorophenylhydrazone but not by dicyclohexylcarbodiimide, suggesting that the AlaE‐mediated l‐alanine extrusion was driven by proton motive force. Based on these results, physiological roles of the l‐alanine exporter are discussed.